Sanity & Tallulah: Shortcuts - Book 3 Shortcuts - Brooks, Molly (Molly Grayson) (New York : Little, Brown and Company, 2021)
When most of the adults on space station Wilnick come down with the flu, Sanity and Tallulah are tasked with delivering turbopumps to another station, but when they take a shortcut, they accidentally end up on the other side of the blockade.
Keywords: Space stations -- Comic books, strips, etc; Space stations -- Fiction; Science fiction; Cartoons and comics; Comics (Graphic works); Science fiction comics